2020
DOI: 10.1371/journal.pone.0238939
|View full text |Cite
|
Sign up to set email alerts
|

Association between the use of colistin for short-term treatment of Gram-negative bacterial infections and the emergence of colistin-resistant Enterobacteriaceae in swine from selected swine farms in Thailand

Abstract: Long-term use of colistin for preventing Gram-negative bacterial infections in food animals was prohibited in Thailand in 2017, but it is permitted for short-term treatment. This study aimed to investigate association between the use of colistin for short-term treatment of infection and the emergence of colistin-resistant Enterobacteriaceae in swine. The current study was conducted at 2 selected swine farms in Thailand. Neither farm has used colistin to prevent infection for longer than 1 year. Rectal swabs we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…Expression of some potentially important genes, such as mcr-1, mcr-9, and mcr-10, was not been detected in the piglet gut following colistin treatment. Previous research reported that short-term treatment with colistin is correlated with the emergence of colistin-resistant Enterobacteriaceae in swine (43). The mcr-1 gene was detected in colistin-resistant S. enterica 4, [5],12:i:-isolate from apparently healthy finishing pigs (44).…”
Section: Discussionmentioning
confidence: 91%
“…Expression of some potentially important genes, such as mcr-1, mcr-9, and mcr-10, was not been detected in the piglet gut following colistin treatment. Previous research reported that short-term treatment with colistin is correlated with the emergence of colistin-resistant Enterobacteriaceae in swine (43). The mcr-1 gene was detected in colistin-resistant S. enterica 4, [5],12:i:-isolate from apparently healthy finishing pigs (44).…”
Section: Discussionmentioning
confidence: 91%
“…2) to a point were weaned piglets were treated more than 60 out of 100 days in October 2016. This is not a sustainable situation from an animal welfare point of view, a financial perspective of the farmer and the perspective of emerging antimicrobial resistance against polymyxins [39][40][41]. Because antimicrobial therapy only reduces shedding once treatment of clinically sick pigs has started, untreated pigs can shed Salmonella, resulting in rapid spread to other compartments and corridors of the farm.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies (Nguyen et al, 2016;Poolperm et al, 2020) have suggested an association between AMU and colistin resistance of Enterobacterales isolated from food-producing animals in Southeast Asia.…”
Section: Main Findingsmentioning
confidence: 99%